Within-session reliability and comparison in resisted sprint performance with the 1080 Sprint between belt and harness attachment points - Sašek, Matic (Kinesiologia Slovenica, 2025)
The application of resistance over the shoulder or hips during resisted sprints could influence performance outcomes but has not been thoroughly investigated. This study examined the within-session reliability of sprint performance measures and compared the outcomes of 1080 Sprint device between belt (hips) and harness (shoulders) attachment. Twelve student-athletes completed three 20 m sprints with resistance equivalent to 25% of body mass (14.0 to 24.7 kg). Sprint split times (5 m, 10 m, 15 m, 20 m), peak velocity, and distance at peak velocity were recorded with 1080 Sprint. Within-session reliability was assessed using intraclass correlation coefficients (ICC3.1) and coefficients of variation (CV), while differences in performance were analysed using paired t-tests and effect sizes (ES). Reliability was excellent for all variables (ICC3.1? 0.93; CV ? 3.08 %) except distance at peak velocity, which showed poor reliability (ICC3.1? 0.32; CV ? 17.2 %). Sprint times and peak velocity were faster with the belt attachment (ES ? 0.93), while peak velocity was reached earlier with the harness attachment (ES = 0.65). Both attachment points provided reliable measurements, but the belt consistently resulted in faster 20 m sprint performance. Coaches and practitioners should consider these differences when assessing resisted sprint performance or prescribing training to ensure consistent and individualized loading strategies
Keywords: resistance; resisted sprint; speed assessment; sprint performance; sprinterska zmogljivost; sprinti proti uporu; upor; vrednotenje hitrosti